1997
DOI: 10.1086/310660
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a High-Velocity Carbon-rich Layer in the Type I[CLC]a[/CLC] SN 1990N

Abstract: We use a parameterized spectrum-synthesis code to make a direct analysis of a high quality spectrum of the Type Ia SN 1990N that was obtained by Leibundgut et al. 14 days before the time of optical maximum. We suggest that the absorption feature observed near 6040 Å, which has been attributed to blueshifted 6355 of Si II, actually was produced by blueshifted 6580 of C II, in a high-velocity (v Ͼ 26, 000 km s Ϫ1 ) carbon-rich region. Implications for SN Ia explosion models are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 36 publications
2
102
0
Order By: Relevance
“…Evidence has been presented for the strongest optical C ii line, l6580, in SN 1998aq (Branch et al 2003), SN 1990N (Jeffery et al 1992;Mazzali 2001), SN 1999ac (Garavini et al 2005), and SN 1994D and SN 1996X (Branch et al 2003 and Paper I). Thomas et al (2007) presented the most convincing evidence in SN 2006D.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Evidence has been presented for the strongest optical C ii line, l6580, in SN 1998aq (Branch et al 2003), SN 1990N (Jeffery et al 1992;Mazzali 2001), SN 1999ac (Garavini et al 2005), and SN 1994D and SN 1996X (Branch et al 2003 and Paper I). Thomas et al (2007) presented the most convincing evidence in SN 2006D.…”
Section: Discussionmentioning
confidence: 97%
“…For SN 1994D, we fit it in the conventional way, with a simple PV Si ii component (a fit is shown in Paper I). For SN 2003du, the feature appears to consist of two marginally resolved components (Stanishev et al 2007), so we use The unusual, nearly flat-bottomed 6100 Å absorption of the early spectrum of SN 1990N has been discussed by several authors (Jeffery et al 1992;Fisher et al 1997;Mazzali 2001). Mattila et al (2005) showed that the 1 week premax spectrum of SN 2001el resembled the early spectrum of SN 1990N (see their Fig.…”
Section: Core-normal Sne Iamentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of IMEs is confirmed by fitting the spectrum with the SN spectrum-synthesis code SYNOW (Fisher et al 1997). Although SYNOW has a simple, parametric approach to creating synthetic spectra, it is a powerful tool to aid line identifications (see Paper I for details).…”
Section: Maximum-light Spectrummentioning
confidence: 99%
“…Signatures of carbon might also be detected as C III λ4649 in so-called "Shallow Silicon" SN Ia that display spectral signatures of overall higher ionization species, e.g., SN 1991T and 1997br (Hatano et al 2002;Garavini et al 2004;Parrent et al 2011;Zheng et al 2013;Scalzo et al 2014b). Seemingly smaller amounts of unburned material of the C+O progenitor, or burned material of the He+C+O progenitor, are frequently detected for so-called "Core Normal" SN Ia (Jeffery et al 1992;Fisher et al 1997;Branch et al 2005; Thomas et al 2007), while signatures of C I λ10691 are detected for several events, and possibly all SN Ia (Höflich et al 2002;Marion et al 2015;Hsiao et al 2015).…”
Section: Introductionmentioning
confidence: 99%